(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
Candesartan is an angiotensin II receptor blocker with inherent low bioavailability. The present studies entail the optimization and evaluation of self- nanoemulsifying drug delivery system (SNEDDS) of Candesartan in order to enhance its oral bioavailability. For this Capryol 90, Captex 500, Labrasol were used as oil, surfactant and co surfactant respectively. FTIR studies revealed no interaction among the drug and polymers used in the formulation. Based on the physicochemical parameters and in-vitro dissolution studies, F17 prepared with Smix (Surfactant: Co-surfactant) of 3:1 and Oil:Smix of 6:4, was found to be an optimum one. The formulation F17 was found to release 99.12 ± 5.10% drug at the end of one hour and scanning electron microscopic analysis showed nanosized particles. The droplet size of the optimized formulation was found to be 51.7 nm & Z-Average of 59.2 nm. The zeta potential of the optimized formulation (F17) was found to be -15.5 mV. The formulations were also found to be stable over a period of 6 months of testing. From in vivo bioavailability studies Cmax of the SNEDDS 35.2 ± 0.02 ng/ml was significant (p<0.05) as compared to the pure drug suspension formulation 25.1 ± 0.03ng/ml. Tmax of both SNEDDS formulation and pure drug suspension was 1.00 ± 0.03 h and 2.00 ± 0.01 h, respectively. AUC is an important parameter in evaluating bioavailability of drug from dosage form, AUC0-∞ infinity for SNEDDS formulation was higher (160.1±1.04ng. h/ml) than the pure drug suspension formulation 135.3 ± 2.02 ng.h/ml. Statistically, AUC0-t of the SNEDDS formulation was significantly higher (p<0.05) as compared to pure drug suspension formulation. Higher amount of drug concentration in blood indicated better systemic absorption of Candesartan from SNEDDS formulation as compared to the pure drug suspension formulation. The results from this study suggest the requirement for potential use of candesartan as self-nanoemulsifying drug delivery systems.